In‐vivo three‐dimensional knee kinematics during daily activities in dogs. Issue 11 (20th May 2015) - Kim, Stanley E.; Jones, Stephen C.; Lewis, Daniel D.; Banks, Scott A.; Conrad, Bryan P.; Tremolada, Giovanni; Abbasi, Abdullah Z.; Coggeshall, Jason D.; Pozzi, Antonio
ABSTRACT: The canine knee is morphologically similar to the human knee and thus dogs have been used in experimental models to study human knee pathology. To date, there is limited data of normal canine 3D knee kinematics during daily activities. The objective of this study was to characterize 3D in‐vivo femorotibial kinematics in normal dogs during commonly performed daily activities. Using single‐plane fluoroscopy, six normal dogs were imaged performing walk, trot, sit, and stair ascent activities. CT‐generated bone models were used for kinematic measurement using a 3D‐to‐2D model registration technique. Increasing knee flexion angle was typically associated with increasing tibial internal rotation, abduction and anterior translation during all four activities. The precise relationship between flexion angle and these movements varied both within and between activities. Significant differences in axial rotation and coronal angulation were found at the same flexion angle during different phases of the walk and trot. This was also found with anterior tibial translation during the trot only. Normal canine knees accommodate motion in all planes; precise kinematics within this envelope of motion are activity dependent. This data establishes the characteristics of normal 3D femorotibial joint kinematics in dogs that can be used as a comparison for future studies. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1603–1610, 2015.